The Dorian Gray phenomenon in financial markets - MAKHIJA, Ajay (Institutional Knowledge at Singapore Management University, 2020)
Looking at the current state of the global economy and the extent of financial market hedonism through the lens of Oscar Wilde’s “The Picture of Dorian Gray”.